EVOLUTION AS NATURE'S TRAJECTORY FROM COMPUTATION TO NARRATION. - Dace, Ted (Cosmos & History, 2022)
Because the basis of physical order is temporal, evolution and narrative are naturally emergent and not inexplicable anomalies in a universe predetermined by timeless mathematical principles. The temporal world of life and consciousness has no place in classical physics but is perfectly at home in a quantum context. In and of itself an atom is the continuous computation of outcomes of potential interactions. The central mystery of quantum mechanics is cleared up by replacing measurement with temporal instantiation as the mechanism by which nature coughs up the determinate world of the senses. In contrast to the continuous time of natural computation - whether atomic, biological or symbolic - the time of classical physics is a succession of discrete instants. As Bergson noted, theorists tend to spatialize this succession into a static sequence. No such operation is possible with unbroken flux and the memory and purpose implicit in it.